A Review of Lighting Programs for Broiler Production - Olanrewaju, H.A.; Thaxton, J.P.; Dozier III, W.A.; Purswell, J.; Roush, W.B.; Branton, S.L. (International Journal of Poultry Science, 2006)
Genetic selection of broilers for rapid growth has resulted in greater final BW and improved feed conversion efficiency in reduced time increments. However, accelerated growth rates are associated with several undesirable traits, including increased fat deposition, and higher incidence of metabolic diseases, visual anomalies, skeletal deformities, and circulatory problems. These deficiencies, as well as the associated financial losses, have led to increased interest in developing management techniques that will maximize productivity while minimizing associated problems of broilers. Light is an important parameter of poultry production. Currently, there are a wide variety of lighting programs (wavelength, intensity, and duration) and devices available to poultry producers, each possessing its own characteristics and applicability to rearing poultry. The potential for changing photoperiods to influence broiler productivity and health is receiving considerable investigation. Some lighting programs have a central purpose of slowing the early growth rate of broilers thus allowing birds to achieve physiological maturity before maximal rates of muscle mass accretion. The aim of this review is to update research on lighting programs for broiler production and to give direction for future lighting research.